Understanding Contributor to Developer Turnover Patterns in OSS Projects: A Case Study of Apache Projects. (19th January 2014) - Iqbal, Aftab
Abstract : OSS projects are dynamic in nature. Developers contribute to a project for a certain period of time and later leave the project or join other projects of high interest. Hence, the OSS community always welcomes members who can attain the role of a developer in a project. In this paper, we investigate contributions made by members who have attained the role of a developer. In particular, we study the contributions made by the members in terms of bugs reported, comments on bugs, source-code patch submissions, and their social relation with other members of an OSS community. Further, we study the significance of nondevelopers contribution and investigate if and to what extent they play a role in the long-term survival of an OSS project. Moreover, we investigate the ratio of contributions made by a member before and after attaining the role of a developer. We have outlined 4 research questions in this regard and further discuss our findings based on the research questions by taking into account data from software repositories of 4 different Apache projects.